Quality Assurance in Qualifications Frameworks : Conference Proceedings, Dublin Castle 12-13 march 2013 - (:unkn) unknown (My University, 2013)
"This report presents the proceedings of the conference "Quality Assurance in Qualifications Frameworks" hosted by Quality and Qualifications Ireland (QQI) on the 12 and 13 March 2013 in Dublin Castle, as part of the Irish Presidency of the Council of the European Union. (...) The aim of the conference was to explore how qualifications frameworks and quality assurance arrangements can best work together at a national and European level in order to achieve the goals of reform in education across the EU and within its member states." (Hrsg., BIBB-Doku)
Dearbhú Cáilíochta i gcreataí Cáilíochtaí : Imeachtaí comhdhála
Keywords: S 1 Stufen der Berufsbildung; L 6.2 Qualitätsmanagement/Qualitätssicherung; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; Qualitätssicherung; Bildungssystem; Europäischer Qualifikationsrahmen; Nationaler Qualifikationsrahmen; EU-Bildungspolitik; Europa